2016
DOI: 10.1057/jit.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Empirical Business Services Sourcing Literature: An Update and Future Directions

Abstract: The 2010 Journal of Information Technology (JIT) article, ‘A Review of the IT Outsourcing Empirical Literature and Future Research Directions,’ analyzed 741 findings on the determinants of Information Technology Outsourcing (ITO) decisions and outcomes from 164 empirical articles published between 1992 and 2010. Using the same coding method, the 2011 JIT article, ‘Business Process Outsourcing Studies: A Critical Review and Research Directions,’ analyzed 615 findings on the determinants of Business Process Outs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 278 publications
(378 reference statements)
5
121
0
6
Order By: Relevance
“…Recent bank cybersecurity issues and software failures in air transport systems, for example, seriously harmed corporate reputation and customer confidence in the organizations involved (Rayner 2014;Shirbon 2016). There is also now considerable evidence of large-scale outsourcing both enabling and also disabling the execution of business strategies (Lacity, Khan and Yan, 2016;Willcocks, Lacity and Sauer, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent bank cybersecurity issues and software failures in air transport systems, for example, seriously harmed corporate reputation and customer confidence in the organizations involved (Rayner 2014;Shirbon 2016). There is also now considerable evidence of large-scale outsourcing both enabling and also disabling the execution of business strategies (Lacity, Khan and Yan, 2016;Willcocks, Lacity and Sauer, 2017).…”
mentioning
confidence: 99%
“…Some sources estimate the failure rate for inter-organizational relationships to be as high as 70 percent (Barringer and Harrison 2000;Hughes and Weiss 2007). In the specific context of BSO relationships, a review of 1,304 empirical findings from 20 years of academic research found 30 percent of client-reported BSO outcomes were negative or unbeneficial (such as poor service quality, significant hidden costs and/or poor customer satisfaction) and 21 percent of client-reported findings resulted in no demonstrable impact on BSO outcomes as a consequence of outsourcing (Lacity et al 2016). BSO failure rates as high as 50 percent have been reported (e.g., Gefen et al 2008;Mani et al 2012).…”
mentioning
confidence: 99%
“…new parties). We expand on the analysis of governance forms in literature involving dyadic outsourcing relationships (Kim, Lee, Koo, & Nam, 2013;Lacity et al, 2016). Our findings contribute to the research by Wiener and Saunders (2014), which identified critical enablers to manage the delicate balance between vendor competition and cooperation (i.e.…”
Section: Business Networkmentioning
confidence: 83%
“…The aim of our research has been to focus on how actors operating in a global IT multisourcing arrangement share information, knowledge and value to create and capture common value, and what are the barriers that may hinder common value creation? In doing so, we responded to the call by Bapna et al (2010) and Lacity et al (2016) for more research into IT multisourcing outcomes. We used the concepts of ecosystems and BM thinking to study the creation and capturing of common value and to identify potential ecosystem barriers.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation